Konektivitas Moda Transportasi Pete-Pete dan BRT di Kota Makassar - Muh Khoiril; Muh Yamin Jinca; Muh Fathien Azmy (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
The Mamminasata Regional Spatial Plan (RTRW) explains that the pete-pete network must be developed and large buses with good services will be needed to increase transportation capacity. With this planning policy, it is expected that the community can switch from private vehicles to public transportation and can reduce congestion in Makassar by paying attention to the connectivity of public transportation in serving the community's journey, especially to the activity centers in Makassar City. The purpose of this study is to determine the direction and recommendations for the development of pete-pete and BRT transportation modes in Makassar City. The analytical method used in this study is the origin matrix for the purpose of finding out the movement of the community, especially in trade and service areas as well as the carrying capacity of BRT and pete-pete public transport connections in Makassar City and then linking them to road classes to produce directions and recommendations for connectivity development. The resulting directions were the development of bus stops and the addition of new public transportation lines to support public transport connectivity in Makassar City.